Rectus Muscle Flap-augmented Closures in Wide-gap Exstrophy Bladder - Mir Fahiem-; Vinay Jadhav; Raashid Hamid; Gowhar Mufti; Narendrababu Munianjanappa; Murali Saroja (Wolters Kluwer Medknow Publications, 2024)
Background: Wound dehiscence is one of the main complications in complete primary repair of exstrophy (CPRE). In our pediatric urology unit, we have switched to the use of inferior epigastric artery based rectus abdominis flap cover for abdominal wall closure in addition to measures like osteotomy and postoperative hip spica. Aim: to assess the efficacy of Recus abdominis flap in prevenion of wound dehisence. Methods: This study was conducted from June 2014 to June 2021 comparing two groups of the patients; group I consisted of thirty patients of CPRE with rectus flap repair of abdominal wall (CPRE-RF) and group II consisted of thirty patients with CPRE without rectus flap. Clinical and surgical details, including the outcome with regards to wound dehiscence and continence, were recorded. Results: The mean age of the patients in CPRE-RF was 5 months and that with only CPRE was 4.6 months. Mean pubic diastasis in Group l was 4.8± 1.07 cm and that of Group II was 4.6±1.3 cm. None of the patients in CPRE-RF had wound dehiscence or bladder prolapse while as 6 patients in CPRE alone had wound dehiscence and 1 had bladder prolapse. This difference was statistically significant. Primary bladder continence was achieved in 4 patients in CPRE-RF and 3 patients in CPRE group. Hypospadias had almost similar occurrence in the two groups. One patient in each group had bladder neck fistula. Conclusion: Use of rectus muscle flap in complete Primary Repair ofExtrophy bladder helps in prevention of wound dehiscence and contributes in achievement of final goal of continence in wide gap pubic diatasis.